2020
DOI: 10.21203/rs.3.rs-51350/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kolaviron (Kolaflavanone), apigenin, fisetin as potential Coronavirus inhibitors: In silico investigation

Abstract: The outbreak of COVID-19 caused by SARS-CoV-2 is increasing with an alarming rate of associated frightening mortality without no known approved therapy. The emergence of new infectious diseases and increase in frequency of drug resistant viruses demand effective and novel therapeutic agents. This study investigated the putative inhibitory potentials of apigenin, fisetin, kolaflavanone, and remdesivir towards SARS-COV2 major protease (6LU7) using in silico methods. Pharmacodynamics, pharmacokinetics and toxicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The flavonol fisetin also produced both hydrogen and pi alkyl bonds with the catalytic center of 6YNQ, although its binding energy was somewhat lower than rutin and baicalein. Other studies have reported binding of fisetin with 6LU7 [ 38 ] . Given these results, we propose that a combination of rutin, baicalein and fisetin may produce a synergistic inhibition of both catalytically active residues in 6YNQ, improving its overall inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The flavonol fisetin also produced both hydrogen and pi alkyl bonds with the catalytic center of 6YNQ, although its binding energy was somewhat lower than rutin and baicalein. Other studies have reported binding of fisetin with 6LU7 [ 38 ] . Given these results, we propose that a combination of rutin, baicalein and fisetin may produce a synergistic inhibition of both catalytically active residues in 6YNQ, improving its overall inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in silico study in our laboratory revealed that apigenin displayed a significant binding affinity with the SARS-CoV-2 major protease (6 LU7). The result also suggested that apigenin could be a potential inhibitor of SARS-COV-2 [53].…”
Section: Apigeninmentioning
confidence: 82%
“…Thіѕ ѕhоwѕ thаtkоlаvіrоn соuld bе a prospective drug fоr the еffесtіvе management and/or trеаtmеnt of Parkinson's disease. Kolaviron has been noted to be a potential anti-COVID-19 drug candidate in a computational experimental study aimed to screen phytochemicals in drug repurposing approach to combat COVID-19 [53]. The study employed USCF Chimera in virtual screening and molecular docking for possible inhibitors of SARS-CoV-2.…”
Section: Kolaviron From Garcinia Kola (Guttiferae)mentioning
confidence: 99%
“…The phytochemical screening of garlic has also been reported to have chemical compounds such as saponin, tannin, carbohydrates, cardio glycoside, alkaloids, flavonoid, phlobatannin and glycoside (Pavni et al, 2011). Apigenin and fisetin have also been documented as potential inhibitors of coronavirus-2 in an in silico investigation (Oladele et al, 2020e).…”
Section: Medicinal Plants With Antioxidant Propertiesmentioning
confidence: 99%